Hepatic Issues and Complications Associated With Inflammatory Bowel Disease: A Clinical Report From the NASPGHAN Inflammatory Bowel Disease and Hepatology Committees. Issue 4 (April 2017) - Saubermann, Lawrence J.; Deneau, Mark; Falcone, Richard A.; Murray, Karen F.; Ali, Sabina; Kohli, Rohit; Ekong, Udeme D.; Valentino, Pamela L.; Grossman, Andrew B.; Rand, Elizabeth B.; Jonas, Maureen M.; Saeed, Shehzad A.; et al.
Abstract : ABSTRACT: Hepatobiliary disorders are common in patients with inflammatory bowel disease (IBD), and persistent abnormal liver function tests are found in approximately 20% to 30% of individuals with IBD. In most cases, the cause of these elevations will fall into 1 of 3 main categories. They can be as a result of extraintestinal manifestations of the disease process, related to medication toxicity, or the result of an underlying primary hepatic disorder unrelated to IBD. This latter possibility is beyond the scope of this review article, but does need to be considered in anyone with elevated liver function tests. This review is provided as a clinical summary of some of the major hepatic issues that may occur in patients with IBD.